PREPARATION AND EVALUATION OF COPPER NANOPARTICLES LOADED HYDROGEL FOR BURNS - KUMAR, ASHISH; PANDIT, VINAY; NAGAICH, UPENDRA (International Journal of Applied Pharmaceutics, 2021)
Objective: The present study focuses on the development and optimization of copper nanoparticles (CNPs) loaded hydrogel for the treatment of dermal burn injuries. Methods: CNPs gel was prepared by dispersing the variable concentration of polyvinylpyrrolidone (PVP K30) and hydroxypropyl methylcellulose (HPMC) in distilled water, PEG 400, and copper nanoparticles. factor screening study was performed for identification of influential factors, followed by optimization study using three-factor Box-Behnken design. Results: Optimized nanogel formulation, when compared to normal control (NC), shows a significant reduction of pro-inflammatory cytokines (IL-6 = 39.74 % and TNF-α =49.37%) and increased level of anti-inflammatory cytokines (IL-10 = 30.90%), indicating reduced inflammation. Further, the wound closure rate of CNPs gel shows significant (12.27 %) wound closure as compared to the NC group and complete wound closure (100 %) on the 14th day, indicating accelerated wound healing. Conclusion: the present investigation endorses accelerated scar-free, accelerated wound healing potential of copper nanoparticles gel with anti-inflammatory potential.